2003
DOI: 10.1046/j.1365-2516.2003.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular liver biopsy is safe and diagnostic for patients with congenital bleeding disorders and hepatitis C infection

Abstract: The prevalence of chronic hepatitis C virus (HCV) infection among patients with severe congenital bleeding disorders is as high as 98%. Advances in HCV treatment currently result in sustained virological response rates of > or =50%. Recent recommendations have reaffirmed that liver biopsy, which provides a direct histological assessment of liver inflammation and fibrosis, is still important for accurate diagnosis and therapeutic decision making. Percutaneous liver biopsy is a simple, standardized procedure tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Only two smaller studies (with sample sizes of 6 and 13) have examined the safety of the transjugular approach in patients with congenital bleeding disorders [21,22]. Gupta et al [22] used more aggressive hemostasis prophylaxis, but Dimichele et al [21] used prophylaxis regimens similar to our own. There were no significant bleeding complications noted in either Gupta's or Dimichele's cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Only two smaller studies (with sample sizes of 6 and 13) have examined the safety of the transjugular approach in patients with congenital bleeding disorders [21,22]. Gupta et al [22] used more aggressive hemostasis prophylaxis, but Dimichele et al [21] used prophylaxis regimens similar to our own. There were no significant bleeding complications noted in either Gupta's or Dimichele's cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Only three studies compared length separately in cirrhotic and non-cirrhotic specimens showing no difference using Tru-cut needle in 2, [23,59] and longer specimens in non-cirrhotics using either Menghini or Tru-Cut needle in 1. [67] Only two small series with non-cirrhotic patients [18,37] gave both mean length and mean CPT number: 23 mm with nine CPTs (Menghini); 13.6 mm with six CPTs (Tru-Cut). The mean number of passes was not significantly associated with the mean length (r = 0.34, p = 0.1).…”
Section: Success Ratementioning
confidence: 99%
“…TJLB is usually indicated when PLB is contraindicated due to coagulopathy and/or ascites [2,6], in liver transplant recipients [7][8][9][10][11], and patients with acute liver failure (ALF) [12,13] or congenital clotting disorders [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we diagnosed two patients by performing TJLB. DiMichele et al reported that TJLB is an alternative to the percutaneous approach for patients with bleeding disorders (16 (21). Although rituximab has not been widely utilized for IVL, some studies have found it to be effective (5,(22)(23)(24)(25)(26)(27)(28)(29) …”
Section: T a B L E 3 S T E R O I D Do S E Ch E Mo T H E R A P Y Amentioning
confidence: 99%